Dilema PHK dan Potong Gaji Pekerja Di Tengah Covid-19 - Mohamad Anwar (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:The problem faced by the company during the Covid-19 pandemic was related to the financial crisis. So that forces companies to lay off several workers / laborers or cut salaries. This raises a new polemic, because in the provisions of the legislation concerning employment, it is regulated regarding the mechanism of layoffs for workers or workers of the company where they work. Including provisions related to deduction of salaries of workers / laborers, so it does not appear to violate the rights of workers or laborers.Keywords: Layoffs, Cut Salaries, Covid-19 Abstrak:Dilema yang dihadapi perusahaan pada saat pandemic Covid-19 adalah terkait krisis keuangan. Sehingga memaksa perusahaan untuk melakukan PHK terhadap beberapa pekerja/buruh atau melakukan pemotongan gaji. Hal ini menimbulkan polemik baru. Karena dalam ketentuan peraturan perundang-undangan tentang ketenagakerjaan, diatur mengenai mekanisme PHK bagi pekerja atau buruh dari perusahaan tempat mereka bekerja. Termasuk ketentuan terkait potong gaji pekerja/buruh, sehingga tidak terkesan melakukan pelanggaran hak dari pekerja atau buruh.Kata Kunci: PHK, Potong Gaji, Covid-19